2010
DOI: 10.1515/hf.2010.088
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission measurements and lattice simulations of microfracture events in spruce

Abstract: A statistical lattice model was developed to investigate the energy associated with damage and failure of wood. The model incorporates several important morphological aspects of wood such as grain direction, early wood percentage and grain geometry. The model was developed to investigate progressive damage under enforced boundary displacements and has been adapted to predict fracture energy related phenomena. In this particular study, notched specimens were loaded in uniaxial tension while monitored by a passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…5c), its cumulative AE energy follows an almost exponential increase path (Fig. 8) and hence indicates the nonlinearity in damage evolution (Nagy et al 2010). In the case of plywood materials, the exponential increase in normalized cumulative AE activity (Fig.…”
Section: Acoustic Emission Intensity and Strain Field Formationmentioning
confidence: 83%
“…5c), its cumulative AE energy follows an almost exponential increase path (Fig. 8) and hence indicates the nonlinearity in damage evolution (Nagy et al 2010). In the case of plywood materials, the exponential increase in normalized cumulative AE activity (Fig.…”
Section: Acoustic Emission Intensity and Strain Field Formationmentioning
confidence: 83%
“…Introduced for wood by Landis et al (2002), this distinct view consists of modeling by a series of linear elements similar to the real wooden fibers. It was demonstrated that this approach provides satisfactory results at smaller scales, despite the higher complexity Brought to you by | University of Georgia Libraries Authenticated Download Date | 6/5/15 10:28 PM of construction and calibration (Davids et al 2003;Fournier 2005;Fournier et al 2007;Sedighi-Gilani and Navi 2007;Vasic and Stanzi-Tschegg 2007;Landis and Navi 2009;Nagy 2010;Nagy et al 2010). This approach facilitated the application of additional concepts in numerical wood models such as growth rings, mechanical variability, and heterogeneous failure patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the Continuum Mechanics approach are the classical model proposed by Ottosen, 2 examined later by Voyiadjis, 3 and the contributions of Li et al 4 and Lv et al 5 The lattice discrete element method (LDEM), used in this article, belongs to the second group. Other models that follow this approach were proposed by Schlangen and Van Mier, 6 Krajcinovic and Vujosevic, 7 Sagar and Prasad, 8 Nagy et al 9 and Rinaldi, 10 and Jivkov and Yates 11 and examine the relationships between different lattice arrangements with the material properties of an equivalent continuum, while Mastilovic and Rinaldi 12 present an extensive revision of different versions of the lattice approach.…”
Section: Introductionmentioning
confidence: 99%